Artificial Intelligence in Endodontics - Gordon Lai; Craig Dunlap; Alan Gluskin; Walid B. Nehme; Adham A. Azim (Taylor & Francis Group, 2023)
ABSTRACTBackground In recent years, with advancements in science and technology, artificial intelligence (AI) has been gaining more relevance in the field of dentistry in general, as well as endodontics. AI-guided algorithms have a great potential to better diagnose, treatment plan, and execute endodontic treatments, as well as outcome prediction of the various endodontic treatments. A review of literature was conducted to assess the application of AI in the field of endodontics.Results AI has been used in a variety of clinical applications including the assessment of root canal anatomy, working length, presence of root fractures, and outcome prediction.Conclusion Within the field of endodontics, AI has already been proven to be useful. The evolution of this technology and its continuous application can positively impact the field of endodontics and assist in preserving the natural dentition. Clinical implications: AI is currently being used for specific endodontic applications and possible potential applications in the future horizon.